Advokasi media lokal untuk praktisi media di Kota Bandung - Eni Maryani; Subekti Wirabhuana Priyadharma; Preciosa Alnashava Janitra; Detta Rahmawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
The notion of local media was proposed in Broadcasting Law number 32/2002 to support the democratic process, political decentralization and to revive the local-scale media industry. In addition, local media are also expected to be a source of relevant information for residents and the community. However, various challenges and obstacles in terms of business as well as in terms of policy continue to emerge. This community service has been carried out to journalists and local media practitioners in West Java to disseminate the results of research conducted by the team from Faculty of Communication Science, Universitas Padjadjaran on media policy and the sustainability of local media in Indonesia. In addition to disseminating research results and local media advocacy, we also conducted a Focus Group Discussion (FGD) on various issues surrounding the local media industry, and also to elaborate on the possible partnership between the academics and local media practitioners to maintain the sustainability of the local media industry in West Java. In the future, it is hoped that research collaboration and various other activities can be done consistently and long-term in nature.